Assessing the impact of physical activity on reducing depressive symptoms : A rapid review - Nadia, Samsudin; Richard Peter, Bailey; Siti Nur Aafifah, Hashim; Janet Ann, Fernandez (BioMed Central Ltd., 2024)
Context The prevalence of depression among teenagers is a significant issue worldwide, which calls for a thorough investigation of non-drug treatments. This expedited evaluation examines 24 specifically chosen studies to clarify the correlation between physical activity depression symptoms in teenagers, undertaken following PRISMA principles.